DATA STORAGE MANAGEMENT USING AI METHODS - Funika, Wlodzimierz; Szura, Filip (Computer Science, 2013)
Data management and monitoring is an important issue in scientiﬁc computa-tion. Scientists want to access their data as quickly as possible. Some experi-ments need to store a lot of data which have to be secure. By saying this wemean that this data can not disappear or be damaged also the data storageshould be as cheap as possible. In this paper we present an approach to theautomation of monitoring and management of data storage. We introduce aknowledge based system which is able to manage data, i.e., make decisions onmigrating data, replicating or removing it. We discuss some of the existingsolutions which are popular on the market. In this paper we aim to present oursystem which uses such AI techniques like fuzzy logic or a rule-based expertsystem to deal with data storage management. We exploit in this system acost model to analyze the proposed solutions. The operations performed byour system are aimed to optimize the usage of the monitored infrastructure.